Analisis Secara Umum Penyebab Penyakit Diabetes Mellitus di Kota Medan - Kalifah Fitria Lubis (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Diabetes mellitus is a disease caused by sugar levels in the body caudes by a combination of generic favtors associated with impaired insulin secretion. The aim of the researcher is to find out in general the meaning, causes, and prevention of diabetes mellitus by seeking knowledge from previous researchers. The article research method is the review method by searching articles in research journal databases and searching the internet. The results showed that cause of diabetes is high blood sugar from diabetes occurs due to disturbances in the body and how to prevent it by adopting a healthy life.